Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepercayaan Konsumen pada UD Discho Indah di Tana Toraja - Hendrik Pappang Bonga; Abedneigo Carter Rambulangi; Jens Batara Marewa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to investigate the influence of price and service quality on consumer trust in UD. Discho Indah in Tana Toraja. The research method used is quantitative using a questionnaire distributed to consumers who shop at UD. Discho Indah. The independent variables in this research are Price and Service Quality, while the dependent variable is Consumer Trust. The data analysis technique used is linear multiple regression to test the relationship between these variables. The research results show that both price (X1) and service quality (X2) have a significant influence on consumer confidence (Y) in UD. Discho Indah in Tana Toraja